THE INFLUENCE OF MORAL OBLIGATIONS, SERVICE QUALITY, TAX AUDIT AND TAX SANCTIONS ON PERSONAL TAXPAYER COMPLIANCE - Yasril Ananta Mawardi; Tenriwaru Tenriwaru; Bahar Sinring (Faculty of Economics dan Business, Atma Jaya Makassar University, 2023)
The purpose of this study was to determine the effect of moral obligations, service quality, tax audits and tax sanctions on personal taxpayer compliance at North Makassar Pratama Tax Service Office. The population of this research is taxpayers who are registered at KPP Pratama North Makassar, the sample is determined based on purposive sampling which is calculated using the slovin formula of 100 respondents. The data used in this research is primary data. The data collection technique uses a questionnaire which is distributed to taxpayers registered at North Makassar Pratama Tax Service Office. The results of the study show that moral obligation, service quality, tax sanctions affect taxpayer compliance.